8t+2*t-1=

Simple and best practice solution for 8t+2*t-1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8t+2*t-1= equation:


Simplifying
8t + 2t + -1 = 0

Reorder the terms:
-1 + 8t + 2t = 0

Combine like terms: 8t + 2t = 10t
-1 + 10t = 0

Solving
-1 + 10t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 10t = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 10t = 0 + 1
10t = 0 + 1

Combine like terms: 0 + 1 = 1
10t = 1

Divide each side by '10'.
t = 0.1

Simplifying
t = 0.1

See similar equations:

| X^2+14x-10=0 | | 6x+2*-x-3= | | q(t)=(3t+8) | | 5p-3*2p+4= | | 7r+2*8r= | | y+4*y+3= | | z+7*5z-1= | | (z+7)*(5z-1)= | | 10x-6=6x+14 | | x-5*4=56 | | 6.3=9 | | 3x-9=90 | | 200-3x=33x+24 | | 10-10x=22-17x | | 4(8x-8)=30 | | 4y(y+7)=72 | | 62-2x=8x+2 | | x-3x+10=y+4 | | 6x-18=-96 | | c^2=-15-8c | | 12=6n | | Y=(6x+88) | | 2(3x-7)-4=2(x-3)+12 | | Y=(4x^2) | | -3(-x+7)+5x=-21 | | 6a+17+a-4=41 | | 5y+13=31-4y | | x^2=-.5x-.0625 | | 7x-15=96 | | x^2-26x+120= | | 10-2(3z+4)=-3(6z+5)-7 | | 2m^2+17m+6=0 |

Equations solver categories